Spiritual Symbolism in The Stone Roses (1989): A Barthesian Semiotic Analysis - Axello Balya Putra; Arshyafca Abyan Jatikusumo; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines spiritual symbolism in selected lyrics from The Stone Roses (1989) by The Stone Roses using Roland Barthes’ semiotic framework. Although symbolism has been widely explored in literary texts, alternative rock lyrics have rarely been analyzed through Barthes’ concepts of denotation, connotation, and myth, particularly in relation to spiritual meaning. This qualitative study analyzes four songs: “I Wanna Be Adored,” “Waterfall,” “I Am the Resurrection,” and “She Bangs the Drums.” The findings reveal recurring symbols of water, resurrection, rhythm, and adoration that construct a myth of spiritual self-awakening and collective transcendence. The study positions the album as a poetic text that encodes modern spiritual identity through secular rock expression.